Identification of calcineurin as a predictor of oocyte quality and fertilization competence based on microarray data. (October 2021) - Daei-Farshbaf, Neda; Aflatoonian, Reza; Amjadi, Fatemeh-sadat; Nikniyaz, Hossein; Taleahmad, Sara; Bakhtiyari, Mehrdad
Abstract: Objective: The aim of our study was to detect a biomarker for selection of competent oocytes with acceptable fertilization potential. Calcium ion fluctuation play the most critical role of modulating intercellular signaling pathways in oocyte maturation, egg activation and the egg-to-embryo transition. Since, the stimulatory action of calcium ion is mediated by binding to certain proteins, the calcium/calmodulin-binding genes (CBGs), as the main calcium binding group, was analyzed in detail. Methods: In this work, bioinformatics analysis was conducted on the CBGs of human cumulus cells (CCs) to elucidate a reliable biomarker for fertile oocyte selection. Calcineurin (CaN) or protein phosphatase 3 (PPP3) was selected which consists of a catalytic subunit A with PPP3CA (Aα), PPP3CB (Aβ), and PPP3CC (Aγ) isoforms and a regulatory subunit B. Whereas CaN A regulates calcium ion function, our study gives insights to probable role of related isoforms within human oogenesis process. The presence of CaN A in CCs surrounding growing and mature oocytes was confirmed by western blotting and the expression patterns of related isoforms were examined by reverse transcription-quantitative PCR (RT-qPCR). Results: Our results indicated the increased expression of the catalytic subunit of CaN protein in the CCs of metaphase (M) II oocytes. The expression level of PPP3CB was significantly elevated in CCs of fertile MII compared with those in the germinal vesicle (GV), MI and unfertilized MII oocytes ( P  ≤ 0.05). Conclusion: Elevated level of PPP3CB isoform in the CCs of fertile MII oocyte could be a reliable indication of oocyte fertilization potential. However, further researches are required to introduce CaN Aβ as an appropriate biomarker for oocyte selection in assisted reproduction technique (ART) programs. Graphical Abstract: ga1 Highlights: Catalytic subunit of calcineurin showed a critical role in oocyte maturation and acquisition of fertilization potential. PPP3CA (α isoform) was responsible for transition from metaphase I to metaphase II. PPP3CC (γ isoform) might be indicative of immaturity in human oocytes. PPP3CB (β isoform) could be used as a reliable predictor for the fertile and competent oocyte selection.